If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 18 = 10x + 90 Reorder the terms: 18 + 4x = 10x + 90 Reorder the terms: 18 + 4x = 90 + 10x Solving 18 + 4x = 90 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 18 + 4x + -10x = 90 + 10x + -10x Combine like terms: 4x + -10x = -6x 18 + -6x = 90 + 10x + -10x Combine like terms: 10x + -10x = 0 18 + -6x = 90 + 0 18 + -6x = 90 Add '-18' to each side of the equation. 18 + -18 + -6x = 90 + -18 Combine like terms: 18 + -18 = 0 0 + -6x = 90 + -18 -6x = 90 + -18 Combine like terms: 90 + -18 = 72 -6x = 72 Divide each side by '-6'. x = -12 Simplifying x = -12
| 9+y=27 | | -5+6w=43 | | 7x+3x=10 | | (((24/35)/(6/7+5/9))*(3/4)) | | (((24/35)/(6/7+5/7))*(3/4)) | | ((24/35)/6/7+5/7)*(3/4) | | ((24/35)/6/7+5/7)*3/4 | | 5d-3d-12=4 | | (17/30)1/3 | | x*1.084=3.25 | | 121/2-31/4 | | x*1.084=5.5 | | 1/8+3/4+1/6 | | x*1.084=5 | | x*1.084=6 | | x*1.84=6 | | x*.84=6 | | (p+30)+p+(3p-3p)=1156 | | (P+37)+P+(4P-40)=729 | | 2x+8=316 | | 2x+18=284 | | a+(a-8)+(a-3)=73 | | x+(x-8)+(x-3)=73 | | 8+16+-4=9t+121-6t | | y/10=-21 | | 6p=-18 | | 1.5q-1.9-4.9q=-4.4q-1.5 | | y=(x-2)(x-3)(x-7) | | 0=(x-3)(x-7)(x-2) | | (x+3)(x-3)=7x/4 | | -3x-2x+1=0 | | x(2x+3)+6x^2=9x-1 |